Interleukin-37 Ameliorates Influenza Pneumonia by Attenuating Macrophage Cytokine Production in a MAPK-Dependent Manner - Qi, Feifei; Liu, Mingya; Li, Fengdi; Lv, Qi; Wang, Guanpeng; Gong, Shuran; Wang, Shunyi; Xu, Yanfeng; Bao, Linlin; Qin, Chuan (Frontiers in Microbiology, 2019)
Viral pneumonitis caused by influenza A (H1N1) virus leads to high levels of morbidity and mortality. Given the limited treatment options for severe influenza pneumonia, it is necessary to explore effective amelioration approaches. IL-37 has been reported to inhibit excessive immune responses and protect against a variety of inflammatory diseases. In this study, by using BALB/c mice intranasally infected with A/California/07/2009 (H1N1), we found that IL-37 treatment increases the survival rate and body weight, and reduces the pulmonary index, impaired the lung injury and decreased production of pro-inflammatory cytokines in the BALF and lung tissue. Moreover, IL-37 administration enhanced not only the percentage of macrophages, but also the percentage of IL-18Rα+ macrophages, suggesting that enhanced the macrophages function may improve outcomes in a murine model of H1N1 infection. Indeed, macrophages depletion reduced the protective effect of IL-37 during H1N1 infection. Furthermore, IL-37 administration inhibited MAPK signalling in RAW264.7 cells infected with H1N1. This study demonstrates that IL-37 treatment can ameliorate influenza pneumonia by attenuating cytokine production, especially by macrophages. Thus, IL-37 might serve as a promising new target for the treatment of influenza A induced pneumonia.